Causes of reading and writing difficulties among children with special needs in the lower basic stage from the point of view of their teachers in public schools in Mafraq Governorate - Harahsheh, Nisreen Khaled (Journal of Educational and Psychological Sciences, 2021)
This study aimed to identify the causes of reading and writing difficulties for children of the lower basic stage from the point of view of their teachers in government schools in Mafraq Governorate and to identify the impact of the following variables (gender, years of experience, age, educational qualification), where the descriptive analytical approach was used, and to achieve The aim of the study was to develop a questionnaire consisting of (22) items, it was distributed to (60) male and female teachers, and (50) questionnaires valid for analysis were counted, and their validity and reliability were confirmed by a committee of specialized arbitrators, and after the process of distributing and collecting the questionnaires, they were coded The study showed that the causes of reading and writing difficulties for children of the lower basic stage from the point of view of their teachers in government schools in Mafraq Governorate were the most social reasons, where they were with an arithmetic average (4.09), and then the reasons Biological, where it came with an arithmetic mean (4.002), and then the environmental reasons, which averaged (3.27), and it was found that there are no statistically significant differences at the level of significance (α≤0.05) in the responses of individuals The study sample is about the causes of reading and writing difficulties in the lower basic stage in government schools in Mafraq Governorate according to the variables (sex, the value of its significance level reached (0.31), age, the value of its significance level reached (0.79), and the educational qualification, the value of its significance level reached (0.90)) and it was found that there are statistically significant differences at the level of significance (α≤0.05) in the responses of the study sample members towards the causes of reading and writing difficulties in the lower basic stage in government schools in Mafraq Governorate according to the variable (years of experience). The value of the significance level reached (0.53) Based on the results of this study, the researcher made recommendations, the most important of which is the need to train children to repeat reading and writing long words, the need to work on the integration of the child with his classmates in order to increase his abilities in reading and writing.